PENENTUAN STRATEGI PEMASARAN HASIL TEMBAKAU DI TENGAH NAIKNYA TARIF CUKAI DAN PEREDARAN ROKOK ILEGAL - Perdana, Yendra Dian Putra; Hajir, Ilham Juniedi; Satoto, Imam; Indriasari, Santi; Qomariah, Nurul (Fakultas Ekonomi dan Bisnis, 2024)
The tobacco products industry in Indonesia is facing two big challenges: increasing excise rates and the circulation of illegal cigarettes. An increase in excise rates increases cigarette prices and can reduce demand. On the other hand, illegal cigarettes offer cheaper prices and are competitors to legal products. CV Gagak Hitam is a cigarette company that was founded in 2004 and is still running the tobacco products industry in the form of hand-rolled kretek cigarettes (SKT) and machine-made kretek cigarettes (SKM) amidst rising excise rates and the circulation of illegal cigarettes. This research focuses on determining marketing strategies for tobacco products at CV. Black Crow uses SWOT analysis. The analysis results show that CV. Black Crow has several strengths, such as a strong brand, wide distribution network, and consumer loyalty. However, CV Gagak Hitam also has several weaknesses, such as high prices and a negative image of tobacco products related to health. Opportunities that can be utilized by CV. Black Crow is increasing public awareness of health and the development of digital technology. The threats facing this industry are increasing excise rates, the circulation of illegal cigarettes, and increasingly stringent government regulations. Marketing strategies that can be implemented by CV. Gagak Hitam in the midst of this situation is developing innovative products at competitive prices, strengthening brand image and increasing consumer awareness, utilizing digital technology to reach consumers and increase marketing efficiency, as well as working with the government to overcome the circulation of illegal cigarettes. Keywords: tobacco products; excise rates; illegal cigarettes; marketing strategy swot analysis.